Dietary aspects at the population and individual level of Pimelodus argenteus, a native fish species from the southern Pantanal, Brazil - Kliemann, Bruna Caroline Kotz [UNESP]; Alvares, Nayara Yuri Mitsumori [UNESP]; Franceschini, Lidiane [UNESP]; Miguel, Bianca da Silva [UNESP]; Neto, Aymar Orlandi [UNESP]; Ramos, Igor Paiva [UNESP] (Boletim do Instituto de Pesca, 2024)
Pantanal is highly important environmentally and economically and suffers from environmental changes and anthropization. Pimelodus argenteus is a native species from the southern Pantanal and important for artisanal fishing and feeding of riverside populations. Given the assumptions, this study aimed to characterize the diet and feeding habits of P. argenteus and verify if there is variation and individual specialization in the diet in the evaluated period. For this, the specimens were acquired from an artisanal fisherman in October 2017 in the Miranda River, southern Pantanal, Mato Grosso do Sul state, Brazil. The population’s diet was variable, composed of 18 food items, and its trophic guild was determined as carnivorous/malacophagous. We observed individual variation and specialization in the diet at the individual level. The consumption of bivalves with high invasive potential and non-organic items was also observed, indicating anthropic influences. These results raise questions about the possible long-term impacts on the native and economically important species. In addition, we suggest that individual specialization may have occurred in response to competitive pressures. Finally, our results can contribute to ecological information and support conservation plans for this native species and this biome with important ecosystem functions.
Aspectos alimentares a nível populacional e individual de Pimelodus argenteus, uma espécie de peixe nativa do Pantanal Sul, Brazil
Keywords: Biosphere reserve; Fish, Populational diet; Individual specialization; Individual variation; World heritage site